The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11242-014-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Viscosity on Relative Permeabilities Derived from Spontaneous Imbibition Tests

Abstract: Spontaneous imbibition experiments are usually carried out on All Faces Open or One End Open cores and this severely limits the information that can be obtained because imbibition can be approximately described with a square root of time function, which involves only a single variable. Two Ends Open with one end in contact with the brine and the other end in contact with oil (at the same pressure) offers much more varied behaviour because imbibition is partly co-current and partly counter-current. Previously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…However, many matrix blocks are partly covered by water in fractured reservoirs (Bourblaux, 1990;Pooladi-Darvish and Firoozabadi, 2000). Haugen et al (2014Haugen et al ( , 2015 designed a special experimental setup to study SI in the core partly covered by water, in which one end of the core was in contact with water and the other end of the core was in contact with oil. In these experiments, initially oil was produced by combination of counter-and cocurrent imbibition from inlet and outlet of the end face.…”
Section: Experimental Methods For 1d Imbibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many matrix blocks are partly covered by water in fractured reservoirs (Bourblaux, 1990;Pooladi-Darvish and Firoozabadi, 2000). Haugen et al (2014Haugen et al ( , 2015 designed a special experimental setup to study SI in the core partly covered by water, in which one end of the core was in contact with water and the other end of the core was in contact with oil. In these experiments, initially oil was produced by combination of counter-and cocurrent imbibition from inlet and outlet of the end face.…”
Section: Experimental Methods For 1d Imbibitionmentioning
confidence: 99%
“…A little time later, oil production from inlet end face ceased and oil was only produced from the outlet end face by co-current imbibition. The fractions of oil production by co-and countercurrent imbibition depend on the oil-water viscosity ratio (Haugen et al, 2015;. Meng et al (2015 and Hauglan (2016) conducted the similar imbibition experiments with unconsolidated porous media (Fig.…”
Section: Experimental Methods For 1d Imbibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2006) reported that the capillary back pressure in oil/air case is about 2/5 down to 1/3 and in the water/oil case about 1/4 down to 1/9 of the capillary driving pressure at the imbibition front for Berea sandstone. Haugen et al (2014Haugen et al ( , 2015 reported that capillary back pressure for Portland chalk in brine/oil case is almost half of the capillary driving pressure at the imbibition front. Fernø et al (2015) reported that the capillary back pressure for chalk is 1/3 and 2/5 of the capillary driving pressure at the imbibition front.…”
Section: Parameter Values and Characteristics Of The Base Casementioning
confidence: 99%
“…Recently, many research groups have investigated various aspects of spontaneous imbibition by experimental (Zhang et al 2014;Meng et al 2015), analytical (Cai et al 2010;MirzaeiPaiaman and Masihi 2013) and numerical method (Wang et al 2008;Mirzaei-Paiaman et al 2011b). The specific items include the form of imbibition front (Akin et al 2000;Zhou et al 2002;Fernø et al 2013), the capillary driving pressure at the imbibition front (Li et al 2009(Li et al , 2011b, the capillary back pressure at the open face of the core (Li et al 2006;Haugen et al 2014), the relative permeability to wetting and non-wetting phase (Mason et al 2010a;Haugen et al 2015;Meng et al 2015), initial water saturation (Baldwin and Spinler 2002), geometric shape of core (Yildiz et al 2006) and boundary condition (Mason et al 2009a). For the investigation of spontaneous imbibition, the selection of which boundary conditions to apply is a significant problem.…”
Section: Introductionmentioning
confidence: 99%